Nerve Regeneration with a Scaffold Incorporating an Absorbable Zinc-2% Iron Alloy Filament to Improve Axonal Guidance - Tomer Ron; Avi Leon; Alon Kafri; Ahmed Ashraf; John Na; Ashvin Babu; Runima Banerjee; Hunter Brookbank; Saimahesh Raju Muddaluri; Kevin J. Little; Eli Aghion; Sarah Pixley (MDPI AG, 2023)
Peripheral nerve damage that results in lost segments requires surgery, but currently available hollow scaffolds have limitations that could be overcome by adding internal guidance support. A novel solution is to use filaments of absorbable metals to supply physical support and guidance for nerve regeneration that then safely disappear from the body. Previously, we showed that thin filaments of magnesium metal (Mg) would support nerve regeneration. Here, we tested another absorbable metal, zinc (Zn), using a proprietary zinc alloy with 2% iron (Zn-2%Fe) that was designed to overcome the limitations of both Mg and pure Zn metal. Non-critical-sized gaps in adult rat sciatic nerves were repaired with silicone conduits plus single filaments of Zn-2%Fe, Mg, or no metal, with autografts as controls. After seventeen weeks, all groups showed equal recovery of function and axonal density at the distal end of the conduit. The Zn alloy group showed some improvements in early rat health and recovery of function. The alloy had a greater local accumulation of degradation products and inflammatory cells than Mg; however, both metals had an equally thin capsule (no difference in tissue irritation) and no toxicity or inflammation in neighboring nerve tissues. Therefore, Zn-2%Fe, like Mg, is biocompatible and has great potential for use in nervous tissue regeneration and repair.